Higher Education Students’ Assessments towards Gamification and Sustainability: A Case Study - Santos-Villalba, María Jesús; Leiva-Olivencia, Juan José; Ramos Navas-Parejo, Magdalena; Benítez-Márquez, María Dolores (MDPI, 2020)
Some academics are pushing for teaching staff to implement didactical practices to obtain sustainable behavior. Moreover, a fundamental element of gamification in all educational stages is the noteworthy effect it has on student motivation. In our study, we examined higher education students’ assessments in the University of Malaga on the design of educational gamification and the teaching criteria that relate to gamification, and its effect on student’s motivation, the applications of gamification, and the attitude towards sustainability. A questionnaire was administered to students studying for degrees in education from the University of Malaga. A total of 187 valid surveys were obtained. Partial least squares structural equation modeling was computed for these data based on an exploratory–confirmatory model and using SmartPLS version 3.3.2. A positive relationship between assessment of students’ motivation and sustainability attitude was found. We found that the opinions of the students about the role of their training and teaching design material in education would affect students’ motivation and the sustainability behavior, although the power of this last construct is moderate.
Keywords: Enseñanza superior; Gamificación; gamification; motivation; attitude; sustainability attitude; PLS-SEM; higher education; mediation